Postoperative Ketorolac Administration Is Not Associated with Hemorrhage in Cranial Vault Remodeling for Craniosynostosis. Issue 8 (August 2019) - Tuncer, Fatma; Knackstedt, Rebecca; Murthy, Ananth; Patel, Niyant
Abstract : Background: Nonsteroidal anti-inflammatory drugs have been used as part of multimodal postoperative analgesic regimens to reduce the necessity of opioids. However, due to its effect on platelet function, there is a hesitation to utilize ketorolac postoperatively. The goal of this study is to analyze our experience utilizing ketorolac in patients who underwent major cranial vault remodeling (CVR) for craniosynostosis with an emphasis on postoperative hemorrhage and complications. Methods: A retrospective review was performed for all patients undergoing CVR for craniosynostosis from 2013 to 2017. Primary outcomes were hemorrhagic complications. Secondary outcomes included length of stay, emesis, and doses of pain medication. Results: Seventy-four consecutive patients met inclusion criteria. Forty-three (58.1%) received ketorolac. Seven in the ketorolac group (16%) and 9 in the control group (29%) received intraoperative blood transfusion ( P = 0.25). One in the ketorolac group (2.3%) and 2 in the control group (3.1%) necessitated postoperative transfusion ( P = 0.56). Patients who received ketorolac required less morphine doses (2.1 versus 3.3 doses; P = 0.02) and had a reduced length of stay (2.1 versus 2.6 nights; P = 0.04). Conclusions: This is the first study to demonstrate that postoperative ketorolac is not associated with an increase in hemorrhagic complications or transfusion risk in children who underwent CVR for craniosynostosis. Patients administered ketorolac required less morphine and had a hospital length of stay. We hope this study stimulates more well-done prospective trials analyzing the role that ketorolac can play in an effective and safe postoperative analgesia regimen.